IDENTITY IN DIASPORIC FICTIONS: A STUDY ON NAFISA HAJI’S THE WRITING ON MY FOREHEAD (2009) - Lakhyajit Nath (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The concept of ‘diaspora’ is derived from the Jews in Palestine before their permanent settlement. Though it relates the physical movement from one place to another, it is also linked to the psychological, mental, societal, religious notions of every migrant individual. So, diaspora means the communities who share the same beliefs and values and who are forced to or voluntarily leave their homelands and settle in a ‘new land’. This phrase therefore includes many terms like refugee, migrants and so on. These people maintain a tight relationship with the places where he or she was born and was attached emotionally or psychologically with the belief, traditions and values provided by the “home land”. The aim of this paper is to give a brief description about identity crisis in Asian American diasporic fiction with the references to Nafisa Haji’s The Writing on My Forehead. Though the narrative of the novel is basically about the Pakistani immigrants in America and England, the novelist depicted the Indian Pakistani diaspora during the partition of India in 1947. Most of the Asian American novels deal with such issues like diaspora, multiculturalism, hybridity etc. This paper also focuses the sufferings of the migrant people basically the people who have moved to America from Pakistan. In postcolonial writing the diasporic essence became one of the most important themes.